PENGGUNAAN PRONOMINA DALAM NOVEL PAPUA BERKISAH KARYA SWASTIKA NOHARA - Neni Sihombing (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Communication on literary work considered as uncommunicative of communication, because its interaction is interaction between the readers and the literary works. That communication is a form of language communication. That is the reason to analyze prose/novel. The goal of this this research to tell about personal pronoun on Papua Berkisah novel. Its method is descriptive by using discourse analyzing theory. The result of this research was found personal pronoun that consist of: first person singular (saya, aku, -ku, ku, gue, I, sa) and first person plural (kami, kita, tong), second person singular (kamu, kau, mu, ko, you, lo) and second person plural (kalian), third person singular (ia, dia, -nya) and third person plural (mereka, dong). The first person singular (daku), second person singular (engkau, Anda, dikau), second person plural (kamu, sekalian, Anda sekalian), and third person singular (beliau) were useless in Papua Berkisah novel.